Mycobacterium bovis infection in livestock workers in Ibadan, Nigeria: evidence of occupational exposure (2012)
bovine tuberculosis (TB) is endemic in the cattle population in nigeria. Livestock workers are at risk of mycobacterium bovis infection and unaware of their health status. Objective: to determine the occurrence of pulmonary M. bovis infection among livestock workers. design: a cross-sectional study of livestock traders was conducted for TB through screening of sputum samples using a simple random sampling method coupled with oral interview on the assumption of sub-clinical pulmonary TB infection. specimens were cultured, and the isolates analysed using molecular typing techniques. results: overall, 10% (7/70) of the livestock traders had a positive culture indicative of M. bovis (n = 2) and M. tuberculosis (n = 5) using deletion typing. further spoligotyping analyses of the M. tuberculosis isolates classified the strains as SB1432 and SB09444 and LAM-10 and T1 using respectively www.mbovis.org and spotclust databases. prolonged cough and >3years in the livestock trade were risk factors for infection. conclusion: we confirm that there is undetected pulmonary M. bovis infection among livestock traders in nigeria. further studies on the role of occupationally exposed workers in the transmission of M. bovis infection to the community are required.